Influência da concentração de carboidrato na produção de kombucha. - Leal, Rayrone Suelyton da Silva (2022)
Kombucha is a beverage produced by a traditional fermentation technique involving the fermentation of black, green or oolong tea sweetened by a symbiotic culture of bacteria and yeast (SCOBY). The source of carbohydrates is essential in the fermentative process of kombucha, as this is the substrate for the symbiotic culture of bacteria and yeast. Yeasts convert sugar in alcohol and carbon dioxide, while acetic bacteria produce new layers of cellulose in the SCOBY and also metabolize alcohol produced by yeasts into organic acids. Therefore, the use of an adequate proportion of sugar is important, where too much can result an overly acidic and overly carbonated drink. In this research, the chosen carbohydrate source was crystal sugar, the most common type used in the fermentation of kombucha. Two concentrations of this sugar were also selected to analyze its influence on the kinetics of fermentation and carbonation of kombucha.